Association between anthropometric factors and meningioma risk: A systematic review and meta-analysis - Chao Xu; Chuan Shao; Jing Wang; Xinmin Ding; Nan Wu (PLoS ONE, 2025)
Background Data regarding the association between anthropometric factors and meningioma risk are inconsistent. Our aim was to investigate the association of body mass index (BMI), height, waist to hip ratio (WHR), waist circumference, and meningioma risk through a comprehensive meta-analysis. Methods An extensive review of literature was conducted in PubMed and Embase databases. Random-effects models were used to pool the study-specific relative risk estimates (RRs) and 95% confidence intervals (CIs). Moreover, we employed a dose-response meta-analysis with a one-stage robust error meta-regression (REMR) model. Results We included nine prospective studies for four anthropometric factors listed above and meningioma risk. Compared with normal weight, both overweight (RR:1.11, 95% CI: 1.04, 1.19; P = 0.003, I2 = 0.0%) and obesity (RR: 1.38, 95% CI:1.16, 1.64; P < 0.001, I2 = 54.7%) were statistically significantly associated with meningioma risk. Dose-response analysis showed a nonlinear relationship between BMI and meningioma risk (P = 0.038). For height, a positive association was identified for men (RR:1.30, 95% CI:1.08, 1.56; P = 0.005, I2 = 0.0%) but not women (RR:1.13, 95% CI: 0.94,1.36; P = 0.186, I2 = 49.8%). Highest vs. lowest levels analyses also showed a positive association between meningioma risk and waist circumference (RR:1.89, 95% CI:1.34, 2.66; P < 0.001, I2 = 0.0%) and WHR (RR:1.40, 95% CI:1.00, 1.94; P = 0.048, I2 = 0.0%). Conclusion Our meta-analysis indicates greater height (in men) and excess weight and body fat mass were associated with an increased risk of meningioma. Further prospective studies with particular attention to sex disparity and dose-response analysis are warranted to confirm our observation.